Conducting decolonizing research and practice with Australian First Nations to close the health gap - Pamela Laird; Anne B. Chang; John Jacky; Mary Lane; André Schultz; Roz Walker (BMC, 2021)
Abstract The purpose of this paper is to highlight a perspective for decolonizing research with Australian First Nations and provide a framework for successful and sustained knowledge translation by drawing on the recent work conducted by a research group, in five remote communities in North-Western Australia. The perspective is discussed in light of national and international calls for meaningful and dedicated engagement with First Nations people in research, policy and practice, to help close the health gap between First Nations and other Australians.